Perlindungan Hukum Terhadap Perampasan Aset Pihak Ketiga Dalam Perkara Tindak Pidana Pencucian Uang - Abdullah, Zulfirman; Nainggolan, Marsudin; Ismed, Mohamad (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Money laundering is a form of economic crime with broad impacts, both individually and systemically. This crime often involves third parties who are not directly engaged in the criminal act. One of the primary legal issues that arise is the confiscation of assets belonging to third parties who have no involvement in the crime, raising concerns regarding the protection of their legal rights. This study aims to analyze the existing legal framework, challenges, and potential solutions in providing legal protection for third parties harmed by asset confiscation in money laundering cases. The author employs a normative juridical research method with an analytical approach, referencing theories of criminal liability and legal protection.  This research relies on secondary data, including statutory regulations, legal documents, and judicial decisions, such as the Supreme Court’s Judicial Review Decision No. 365 PK/Pid.Sus/2022 dated May 23, 2022, concerning Andika Surachman and associates (owners of First Travel), and the Supreme Court’s Cassation Decision No. 4101 K/Pid.Sus/2024 dated July 16, 2024, concerning the defendant Rafael Alun Trisambodo. This study also evaluates the relevance of Law No. 8 of 2010 on the Prevention and Eradication of Money Laundering (UU TPPU) in safeguarding the rights of bona fide third parties.  The findings indicate that while the UU TPPU acknowledges the potential involvement of third parties in money laundering cases, its provisions remain limited and do not comprehensively safeguard bona fide third parties. This research identifies solutions to enhance legal protection against arbitrary law enforcement practices, such as revising existing regulations and strengthening the mechanism for objections to asset confiscation. Theoretically, this study contributes to the development of criminal law concepts, particularly regarding the protection of third-party rights in asset confiscation related to money laundering offenses. Practically, the findings of this study are expected to serve as a guideline for policymakers and law enforcement agencies in formulating fairer and more effective legal policies while ensuring that individuals who are not involved in criminal activities remain legally protected